Emotional competences in higher education: a systematic review - Lagos San Martín, Nelly Gromiria (2024)
Introduction: Currently, it is possible to identify scientific evidence that an intentional, gradual and systematic development of emotional competencies in higher education complements the formative process and favors the personal well-being of students. Objective: to analyze the publications that consider the study of emotional competencies in higher education students between 2013 and 2022. Method: This study corresponds to a systematic review of the articles found in the Web of Science, Scopus and SciELO databases. Of the 90 articles initially found, the PRISMA methodology made it possible to reduce them to 26, which are reported in this paper. Results: the main findings indicate that relational studies are the most frequent (n=14). Likewise, the existence of educational programs aimed at promoting emotional competencies in higher education is reported (n=8), which indicates that educational research in this area is at an advanced stage of knowledge. Conclusion: based on these findings, it is possible to conclude that there is a growing scientific interest in promoting emotional education at the university level, based on the wide range of existing theories that support comprehensive training at this educational level.